The Relationship Between Human Resource Management and Teacher Performance in Islamic Education at One Roof Junior High School 3 Sekotong - Nurisah, Nurisah; Citriadin, Yudin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the effect of human resource management (HRM) on teacher performance in the context of Islamic education. The method used was sampling technique with linear regression test, involving a population of teachers at SMP Satu Atap 3 Sekotong. Data were collected through a questionnaire designed to explore the relationship between HRM and teacher performance. The analysis showed a significant correlation with a Pearson Correlation value of 0.882 (p < 0.01), indicating a strong positive relationship. The regression model yielded an R Square of 0.778, indicating that 77.8% of the variation in the management relationship can be explained by teacher performance. ANOVA analysis showed the regression model was significant (F = 27.998, p < 0.001). This finding confirms that effective HRM implementation contributes to improved teacher performance. This study provides important insights for education managers in formulating more effective development strategies to improve the quality of education.